Effects of azadirachtin in Rhodnius prolixus: data and hypotheses - Garcia,E. S. (1991)
The effects of azadirachtin A, a tetranortriterpenoid from the neem tree Azadirachta indica J., on both development and interaction between Trypanosoma cruzi, the causative agent of Chagas' disease, and its vector Rhodnius prolixus were studied. Given through a blood meal, a dose-rsponse relationship of azadirachtin was established using antifeedant effect and ecdysis inhibition as effective parameters. A singlo dose of azadirachtin A was able to block the onset of mitosis in the epidermis and ecdysteroid titers in the hemnolymph, determined by radioimmuneassay, were too low for an induction of ecadysis. The survival of T. cruzi was also studied in R. prolixus treated with the drug. If the trypomastigotes were fed in presence of azadirachtin A the number of parasites drastically decreased. If the drug was applied after infection of the bug with T. cruzi, the parasite was still abolished from the gut. If the insect was pretreated with azadirachtin A before infection the same observation was obtained. A single dose of azadirachtin A was enough for a permanent resistance of the insect host against its reinfection with T. cruzi and for blocking the ecdysis for a long time. The effects of azadirachtin A on the hormonal balance of the host and growth inhibition of the parasite will be discussed on the basis of the present results.